Case Report: Observation of early-onset high myopia with fundus tessellation changes in Coffin–Siris syndrome 9 (CSS9) and literature review - Wu, Ruohao; Li, Yu; He, Zhanwen; Meng, Zhe; Tang, Wenting; Liang, Liyang (Frontiers in Pediatrics, 2025)
Coffin-Siris syndrome 9 (CSS9), a rare congenital disorder caused by SRY-related HMG-box 11 gene (SOX11) deficiency, is characterized by high phenotypic heterogeneity including a wide spectrum of organ anomalies. Pathogenic variants in SOX11 can induce ocular motor disorders and ocular deformities resulting in visual malfunctions. Here, we report a 10-year-old Chinese boy with early-onset high myopia (eoHM) and fundus tessellation changes with cone-rod cells dystrophy who presented with characteristic CSS phenotypes, including coarse facial features, neurodevelopmental disabilities, and fifth finger anomalies. By applying trio-based whole-exome sequencing, we identified a de novo variant in SOX11, NM_003108.4: c.1013 C>T, p. S338l, classified as likely pathogenic. A systematic literature review yielded 14 publications providing detailed data from 57 CSS9 cases. Quantitative analysis of the ophthalmological phenotypic spectrum of the 58 cases (including our proband) revealed that almost half (26/58, 44.83%) presented ophthalmological malformations; the most prevalent phenotype was ocular motor disorder (15/58, 29.31%); however, pathologic fundus change was only reported in our proband (1/58, 1.72%), suggesting that fundus examination may have been lacking in previous investigations of CSS9 cases. In summary, we report a CSS9 patient with eoHM and fundus tessellation changes, suggesting a potential role of SOX11 in fundus oculi development. We recommend ophthalmological examination with fundus screening for individuals with CSS9 presenting with significant visual impairments, as ophthalmological malformation with extensive lesions is a potentially important feature of CSS9.